Calcareous sponges (Porifera, Calcarea) from Florida: new species, new records and biogeographical affinities - Lopes, Matheus V.; Padua, André; Cóndor-Luján, Báslavi; Klautau, Michelle (Zootaxa, 2018)
Florida is among important marine biodiversity areas with high richness and endemism of marine taxa. Despite the economic and scientific importance of the region, knowledge on the diversity and distribution of some groups, such as calcareous sponges, is still reduced and scattered in old literature. In the present work, sponges collected in the Florida Keys were studied under an integrative perspective (traditional morphology and DNA: ITS). Three calcinean species were found: Clathrina smaragda sp. nov., C. lutea, and Ernstia rocasensis. Clathrina smaragda sp. nov. is the first Clathrina described with a green cormus. The occurrence of C. lutea in Florida was confirmed, and E. rocasensis had its geographical distribution widened from the Northeastern Brazilian waters to Florida, although Floridian individuals of this species have presented differences in morphological characters that resulted in the proposition of a new diagnosis and a discussion on morphological plasticity in Clathrinidae. A complete list of the calcareous sponges from Florida is presented and their distributional patterns are discussed.